Cumulene-like bridged indeno[1, 2-b]fluorene π-conjugated polymers synthesized on metal surfaces. Issue 61 (9th July 2021) - Martín-Fuentes, Cristina; Urgel, José I.; Edalatmanesh, Shayan; Rodríguez-Sánchez, Eider; Santos, José; Mutombo, Pingo; Biswas, Kalyan; Lauwaet, Koen; Gallego, José M.; Miranda, Rodolfo; Jelínek, Pavel; Martín, Nazario; et al.
Abstract : Synthesis and characterization by scanning probe microscopy of cumulene-like bridged indeno[1, 2- b ]fluorene π-conjugated polymers on coinage metals. Abstract : Among the plethora of polycyclic structures that have emerged in recent years, indenofluorenes comprise a unique class of compounds due to their potential in organic electronic systems such as OLEDs, OFETs, and OPVCs. However, the synthesis of fully conjugated indenofluorenes without bulky groups on the apical carbons under standard chemistry conditions is not easily accessible. In this regard, on-surface synthesis has appeared as a newly developing field of research, which exploits the use of well-defined solid surfaces as confinement templates to initiate and develop chemical reactions. Here, we demonstrate the successful fabrication of indeno[1, 2- b ]fluorene π-conjugated polymers linked via cumulene-like connections on well-defined metallic surfaces under ultra-high vacuum conditions. The structure and electronic properties of the formed polymers have been precisely characterized by scanning tunneling microscopy, noncontact atomic force microscopy and scanning tunneling spectroscopy, complemented by computational investigations.